Modulation of sympathetic activity and heart rate variability by ivabradine. (22nd June 2015) - Dias da Silva, Valdo Jose; Tobaldini, Eleonora; Rocchetti, Marcella; Wu, Maddalena A.; Malfatto, Gabriella; Montano, Nicola; Zaza, Antonio
Abstract: Aims: Bradycardic agents are currently used in the treatment of angina and heart failure; direct information on their effects on cardiac sympathetic nerve activity (SNA) may be relevant to their chronic use. The present study evaluates the effect of pacemaker inhibition on SNA; direct nerve recordings and indirect autonomic indexes are compared. Methods and results: Experiments were performed in 18 anaesthetized rats. SNA (direct nerve recording) and heart rate variability (HRV) indexes were evaluated in parallel. All parameters were recorded 10 min before to 60 min after administration of the I f blocker ivabradine (IVA; 2 mg/kg, i.v.; n = 8) or vehicle (VEH; n = 5). IVA-induced RR interval (RR) prolongation (at 60 min +15.0 ± 7.1%, P < 0.01) was associated with decreased diastolic arterial pressure (DAP; −17.3 ± 8.4%, P < 0.05) and increased SNA (+51.1 ± 12.3%, P < 0.05). These effects were accompanied by increased RR variance (RR σ 2 ), which showed strong positive correlation with RR. Frequency-domain HRV indexes (in normalized units) were unchanged by IVA. After baroreceptor reflexes had been eliminated by sino-aortic denervation ( n = 5), similar IVA-induced RR prolongation (at 60 min +14.3 ± 5.9%, NS vs. intact) was associated with a larger DAP reduction (−30.9 ± 4.1%, P < 0.05 vs. intact), but failed to affect SNA. Conclusions: (i) IVA-induced bradycardia was associated with increased SNA, resulting from baroreceptor unloading; if this applied to chronic IVA use in humans, it would be of relevance for therapeutic use of the drug. (ii) Whenever mean HR is concomitantly changed, time-domain HRV indexes should not be unequivocally interpreted in terms of autonomic balance.